2021
DOI: 10.3390/molecules26227036
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide: A Herbal-Chemosynthetic Approach for Enhancing Immunity, Combating Viral Infections, and Its Implication on Human Health

Abstract: Plants consistently synthesize and accumulate medically valuable secondary metabolites which can be isolated and clinically tested under in vitro conditions. An advancement with such important phytochemical production has been recognized and utilized as herbal drugs. Bioactive andrographolide (AGL; C20H30O5) isolated from Andrographis paniculate (AP) (Kalmegh) is a diterpenoid lactones having multifunctional medicinal properties including anti-manic, anti-inflammatory, liver, and lung protective. AGL is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Recently, many studies have been conducted worldwide on varieties of traditional medical techniques. Kalmegh ( Andrographis paniculata ), an ayurvedic herb, delivers immunoprotective potential against respiratory viral diseases, including SARS-CoV-2 ( Hiremath et al, 2021 , Mishra et al, 2021 , Wanaratna et al, 2021 ). This study investigated the herbal activity of respiratory infections using a network pharmacology approach ( Banerjee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have been conducted worldwide on varieties of traditional medical techniques. Kalmegh ( Andrographis paniculata ), an ayurvedic herb, delivers immunoprotective potential against respiratory viral diseases, including SARS-CoV-2 ( Hiremath et al, 2021 , Mishra et al, 2021 , Wanaratna et al, 2021 ). This study investigated the herbal activity of respiratory infections using a network pharmacology approach ( Banerjee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In present study, the results demonstrated that Andr promote the growth and immunity of L. vannamei, and protects shrimp against V. alginolyticus by regulating inflammation and apoptosis via a ROS-JNK dependent pathway. Andr being used as a dietary supplement to improve immunity in patients has a long history (48,59,60). In recent years, Andr has also been used as feed additive in animal husbandry (61) and aquaculture (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…It possesses the ability to eradicate various strains of viruses, including Influenza A Virus (IAV), Human Immunodeficiency Virus (HIV), Hepatitis B and C, Herpes simplex virus type I, and EBV ( Intharuksa et al, 2022 ). Andrographis paniculata lactone is clinically employed to treat bacterial infections and stimulates an immune response that aids in combating microbial infections by regulating its complementary system, granulocytes, and macrophages ( Mishra et al, 2021 ; Zhang H. et al, 2021 ).…”
Section: Herbal Medicine Used In the Treatment Of Infectious Diseasesmentioning
confidence: 99%